High treatment adherence, satisfaction, motivation, and health-related quality of life with fingolimod in patients with relapsing-remitting multiple sclerosis – results from a 24-month, multicenter, open-label Danish study - Schreiber K (Patient Preference and Adherence, 2018)
Karen Schreiber,1 Matthias Kant,2 Claudia Pfleger,3 Henrik Boye Jensen,4 Ole Oesterberg,5 Anne Rieper Hald,5 Frederik K Nielsen,5 Sune Rubak6 1Department of Neurology, Rigshospitalet, Copenhagen University Hospital, Copenhagen, Denmark; 2Department of Neurology, Hospital of Southern Jutland, Soenderborg, Denmark; 3Department of Neurology, Aalborg University Hospital, Denmark; 4Department of Neurology, Kolding Hospital, Kolding, Denmark; 5Novartis Pharmaceutical, Copenhagen, Denmark; 6Department of Child and Adolescent Health, Aarhus University Hospital Skejby, Aarhus Denmark Purpose: Treatment adherence is a prerequisite for treatment success and therefore an important consideration to assure that therapeutic goals are achieved both from a patient point of view and for optimal health care resource utilization. Published data on treatment adherence with fingolimod (Gilenya®) are limited. Therefore, this study investigated treatment adherence in patients with relapsing-remitting multiple sclerosis (RRMS) treated with fingolimod in Denmark. Patients and methods: This was a 24-month, multicenter, open-label study, investigating treatment adherence, satisfaction, motivation, and health-related quality of life (QoL) in RRMS patients treated with fingolimod. In addition, the effect of a motivational interview support program on these measures was evaluated. Treatment adherence was assessed by pill count. Treatment satisfaction, motivation, and QoL were assessed by patient-reported outcomes (PROs). Results: A total of 195 patients were enrolled in the study. A very high treatment adherence was observed during the entire study with no statistically significant difference between study visits before (99%) and after (97%) the motivational interview. In accordance, a high level of treatment satisfaction was found in the Treatment Satisfaction Questionnaire for Medication 9, which was scored high throughout the study with the highest scores seen for the convenience domain (ranging from 94.51 to 95.78). Furthermore, additional PROs demonstrated a high health-related QoL, a self-determined form of motivation for taking medication, and a patient perception of an autonomy supportive approach provided by the health care provider, at all study visits. Conclusion: High levels of treatment adherence, satisfaction, motivation, and QoL were observed in Danish RRMS patients treated with fingolimod. As these positive measures were observed at all study visits and throughout the study, no effect of the motivational interview support program was found. Keywords: Gilenya®, multiple sclerosis, treatment adherence, motivational interview, quality of life, Treatment Satisfaction Questionnaire for Medication